UK General Insurance: Changing Distribution Paradigm - Kumar, Shishir (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2009)
UK General Insurance industry is going through structural changes. Increased regulatory burden and rising operating cost are forcing all insurers to reduce the cost and improve the efficiency. In addition, increasing commoditization of underwriting and insurance products and proliferation of “me too” distribution channels are further making it difficult. Hence, insurers are embracing innovative operating model to retain cost. Direct or Virtual distribution- internet- is playing larger role due to lower cost model. Companies are using direct channel as a complimentary to the traditional channel. However, given its associated advantages and consumer willingness will put forth as a dominant distribution channel.